Ischemic Stoke as the Initial Presenting Feature for Acute Myeloid Leukemia with Thrombocytosis - Tampubolon, Eunike Firyanti; Astuti, Febri Sri (Universitas HKBP Nommensen, 2025)
Background : Acute myeloid leukemia (AML) is known to confer complications mainly due to their underlying disease or chemotherapy. Although they are at high risk for a wide variety of hemorrhagic and thrombotic complications, thrombotic vascular complication as an initial manifestation is less common. Cerebral involvement in patients with AML is associated with a five times higher mortality risk. Case : 54-year-old male patient, presenting with left-sided hemiparesis, fever, decreased appetite and laboratory findings showed leukocytosis (40,990/mm3) and thrombocytosis (814,000/mm3). Computed tomography showed a right infarct in the middle cerebral artery territory. The diagnosis of AML emerged during investigated. While conservatively managed, he developed a loss of consciousness and was admitted to the intensive care unit. Discussion : In a case series of 24 patients, thrombotic events were the first clinical manifestation of leukemia in only 3.4% of cases. The association of thrombocytosis with AML is unusual, a few cases have been described with chromosome 3 abnormalities, however, we could not perform a genetic analysis of this case. Pathogenic mechanism in several studies demonstrated a causal relationship between elevated platelet count are associated with an increased risk of vascular occlusion and leukocytosis in the acute phase of the disease produces hyperviscosity causing blood stasis. Conclusion : Thrombotic events in the cerebrovascular system in early cases of AML may occur possibly due to hyperviscosity, and this may increase the risk of death. Lack of facilities in peripheral hospitals causes limited management. Keywords : Ischemic stroke; Acute myeloid leukemia (AML); Thrombocytosis